Occurrence of imidacloprid, carbendazim, and other biocides in Italian house dust: Potential relevance for intakes in children and pets. Issue 9 (2nd September 2017) - Salis, Severyn; Testa, Cecilia; Roncada, Paola; Armorini, Sara; Rubattu, Nicola; Ferrari, Angelo; Miniero, Roberto; Brambilla, Gianfranco
ABSTRACT: The occurrence of pesticides intended for non-agricultural use was investigated in 206 dust samples drawn from vacuum-cleaner bags from residential flats in Italy. The multi-residue analysis targeted on 95 different active principles was performed with UPLC-MS/MS, with a Limit of Quantification (LOQ) of 0.008 μg/g dry weight. The results indicated the presence of imidacloprid (IMI) and carbendazim (CARB) in 30% and 26% of the samples, with a mean and P95 concentration between 1.6 and 39 and between 0.08 and 4.9 μg/g, respectively. Combined presence of two biocides was noted in 19.4% samples, of three biocides in 9.2% samples, of four biocides in 3.4% samples, and of five and six biocides in 0.5% and 1% samples, respectively. According to the estimated dust intake in infants/toddlers aged 6–24 months (16–100 mg d −1 ) and cats (200 mg d −1 ), it was possible to obtain risk characterization with respect to the Acceptable Daily Intake (ADI) for IMI of 0.060 mg/kg body weight (bw) proposed by the European Food Safety Authority (EFSA) and the chronic Population Adjusted Dose (cPAD) of 0.019 mg/kg bw d −1 by US-EPA. Under the worst-case scenario, the presence of IMI in dust indicates potential exceedance of the cPAD in kittens, to be considered as sentinel also accounting for combined exposure. This study highlights the relevance of consumer empowerment about the responsible use of pesticides as biocidal products in indoor environment.